2021
DOI: 10.21929/abavet2021.4
|View full text |Cite
|
Sign up to set email alerts
|

Crecimiento de corderos de pelo en el altiplano semiárido de Zacatecas durante el invierno

Abstract: Crecimiento de corderos de pelo en el altiplano semiárido de Zacatecas durante el invierno

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The BW obtained in Katahdin lambs matches the figures reported by Ehrhardt et al (2018) and Vicente-Pérez et al (2021): 3.7 and 3.9 kg, respectively. Although the BW values reported in this study were obtained using pure breeds, these results match the findings of López et al (2021), who found a similar BW (3.8 kg), when Dorper or Katahdin parental breeds are used. Likewise, Macías et al (2010) have reported that crosses of these paternal breeds with the maternal Pelibuey breed have the advantage of producing offspring for supply with acceptable growth rates.…”
Section: Resultssupporting
confidence: 88%
“…The BW obtained in Katahdin lambs matches the figures reported by Ehrhardt et al (2018) and Vicente-Pérez et al (2021): 3.7 and 3.9 kg, respectively. Although the BW values reported in this study were obtained using pure breeds, these results match the findings of López et al (2021), who found a similar BW (3.8 kg), when Dorper or Katahdin parental breeds are used. Likewise, Macías et al (2010) have reported that crosses of these paternal breeds with the maternal Pelibuey breed have the advantage of producing offspring for supply with acceptable growth rates.…”
Section: Resultssupporting
confidence: 88%
“…Commonly, differences are reported in weight and growth of males and females. In some studies, female and male sheep show differences in weight at weaning, at one year, at maturity, and in the rate of growth (González-Garduño et al, 2002;Hinojosa-Cuellar et al, 2018;López-Carlos et al, 2021). Therefore, differences in the growth curves of both sexes are expected, as appreciated in Figures 1 and 2; as well as in the parameters estimated in the present study, as described by the five nonlinear models (Tables 4 and 5).…”
Section: Discussionmentioning
confidence: 99%